Real word data with no evidence for additional left atrial substrate modification at first PVI procedure in patients with persistent atrial fibrillation: results from the German Ablation registry - Strzelczyk, Elmar; Jilek, Clemens; Brachmann, Johannes; Eckardt, Lars; Kuck, Karl-Heinz; Willems, Stephan; Spitzer, Stefan G.; Straube, Florian; Schumacher, Burghard; Thomas, Dierk; Ince, Hüseyin; Hochadel, Matthias; et al. (Journal of interventional cardiac electrophysiology, 2026)
Pulmonary vein isolation (PVI) is the cornerstone of interventional treatment for atrial fibrillation. Patients with persistent atrial fibrillation have relatively high recurrence rates after catheter ablation irrespective of treatment strategy. Randomized data suggest that adding substrate modification to PVI at the first ablation procedure does not improve arrhythmia-free survival. To date, real-world data from experienced centers is limited.
Gesehen am 12.02.2026